Penerapan Protokol Kesehatan Covid-19 di Pusat Perbelanjaan Kota Bandung dalam Perspektif Undang-Undang Perlindungan Konsumen (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
To reduce the number of Corona Virus Disease 2019 (COVID-19) and maintain economic stability in Indonesia, the government requires consumers and business actors to implement the COVID-19 health protocol in shopping centers. Protection of consumer safety, security and comfort is stated in Article 4 of Law Number 8 of 1999 concerning Consumer Protection. Bandung city has many shopping centers, but there are few studies reporting on the implementation of the COVID-19 health protocol in its shopping centers. This study aims to determine the implementation of the COVID-19 health protocol and the level of knowledge of consumers and business actors at shopping centers in Bandung regarding their rights and obligations during the COVID-19 pandemic. This study used a sociological non-doctrinal approach. The shopping center used as the research sample has met the inclusion criteria. Data was collected by means of observation, questionnaires and literature study and then analyzed using qualitative descriptive methods. The results showed that >70% of consumers knew their rights and obligations, but 36.4% of consumers didn’t wash their hands/use handsanitizer before entering and after leaving the shopping center, 21.2% didn’t access the Peduli Lindungi application, and 46.8% didn’t keep their distance when shopping or use the elevator. Likewise with business actors, almost all of them know their rights and obligations, but they didn’t careful in selecting consumers who can and cannot enter shopping centers. It can be concluded that the majority of consumers and business actors in Bandung shopping centers already know their rights and obligations, but the COVID-19 health protocol has not been implemented optimally.